Resurgence of Selective Industrial Policy: What Turkey Needs - Gokhan Yilmaz (Turkish Economic Association, 2011)
Three decades of Turkish experience with nonselective industrial policies (consistent with neoliberal policy) clearly demonstrates that structural transformation in Turkish economy could not be achieved. In this paper, we have three motivations. Our first motivation is to discuss overall industrial policy developments in Turkey since 1980s. Secondly, we aim to recommend feasible selective industrial policies for Turkey to support structural transformation. Thirdly, we comment on new Industrial Policy Strategy in Turkey. In that respect, our three basic research questions are, firstly, is there still any meaningful space to implement industrial policy in developing countries such as Turkey?, secondly, which policies could be used? and thirdly, what are the main shortcomings of new Industrial Policy Strategy in Turkey?. Our research demonstrates that there is still meaningful space to implement selective industrial policy in developing countries such as Turkey. Moreover, new Turkish Industrialization Strategy needs significant revisions if it genuinely aims at structural transformation in Turkey.
Keywords: O10; O14; O25; 330; Turkey; Industrial Policy; Structural Transformation; Economic Growth.; Turkey; Industrial Policy; Structural Transformation; Economic Growth; Industrialisierungspolitik; Systemtransformation; Wirtschaftswachstum; Türkei